Subclinical cardiac involvement: A subtle foe in the setting of systemic sarcoidosis - Yalta, Kenan; Ozkan, Ugur; Bulburu, Irem B; Gurdogan, Muhammet; Yetkın, Ertan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
.